Electrophysiological remodeling of the right ventricle in experimental heart failure of different etiologies - A. S. Tsvetkova; V. V. Krandycheva; S. N. Kharin (Бюллетень сибирской медицины, 2019)
The aim of the study was to evaluate electrophysiological remodeling of the right ventricle in rats in experimental heart failure of different etiologies. Materials and methods. Isadrin-, doxorubicin- and monocrotaline-induced heart failure models were developed. Unipolar epicardial electrograms of the ventricles (256 recording sites) were recorded using a 144-channel system. The cardiac output and pressure in both ventricles of the heart were measured. Activation-recovery intervals were used as an index of duration of local repolarization, and the general and local dispersions of activation-recovery intervals were used as an index of heterogeneity of ventricular repolarization. Results. In all models of heart failure, the following were identified: 1) non-uniform prolongation of repolarization with the greatest elongation at the apex of the right ventricle; 2) an increase in apicobasal differences of repolarization with the greatest change in the right ventricle; 3) an increase in the heterogeneity of the repolarization of the epicardial layer of the ventricles with heterogeneous changes in the local heterogeneity of repolarization and a decrease in the interregional differences in the heterogeneity of the electrophysiological properties of the myocardium; 4) more pronounced changes in the repolarization of the right ventricle than in the repolarization of the left ventricle. Conclusion. Thus, irrespective of the cause of the heart failure, the following changes occur: 1) prolongation of the right ventricular repolarization occurs non-uniformly (mostly due to the apical area), which results in an increase in the right ventricular repolarization heterogeneity; 2) an increase in the heterogeneity of right ventricular repolarization is observed, which causes an increase in the overall heterogeneity of the ventricular epicardial surface.